Pembinaan Pasca Diklat Untuk Menjaga Nilai-Nilai Integritas Di Tempat Kerja - Bambang Kismanto (Cendekia Niaga, 2019)
This research is an evaluation post-training of anti-corruption subject, that aims to maintain the internalization of integrity values consisting of honest, empaty, independent, disciplined, responsible, hardworking, simple, brave, and fair. evaluation post training is done by various methods including coaching methods, methods of providing motivation both written and audio, and reward method. The method is evaluated using a self-assessment questionnaire. The conclusion of the study states that the method with coaching by mentors and facilitators post-training is more effective to maintain the value of anti-corruption / integrity in the workplace.